The Quality Attributes as Affected by Different Wrapper Treated with Insect Repellent and Fungicide - Nur Zalikha Mohamad Yatim (School of Bioprocess Engineering, University Malaysia Perlis, 2019)
To evaluate the effect of organic insecticide and fungicide to the growth of Harumanis mango. To differentiate the morphology of Harumanis based on the effect of the application compared to untreated paper and fruit. To examine the better wrapper treated with insecticide and fungicide in controlling the pest and disease problem.